2007
DOI: 10.1002/pssb.200642394
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer and neutron‐diffraction studies of LaCo0.42Fe0.58O3–d

Abstract: PACS 61.12. Ld, 72.80.Ga, 76.80.+ y Mössbauer, neutron powder diffraction and magnetization measurements have been performed for the LaCo 0.42 Fe 0.58 O 3-d compounds in the temperature range 4.2 K < T < 400 K. It was found that a stoichiometric compound has a canted G-type antiferromagnetic structure with T N ~ 380 K and magnetic moment of 2.3µ B per formula unit. Combined Mössbauer and neutron-diffraction data give evidence that only Fe 3+ ions are in the magnetically ordered state, whereas Co 3+ ones are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…10 For M = Fe 3+ with filled e g orbitals, powder magnetization measurements, neutron diffraction, and Mössbauer spectroscopy all indicated that the magnetic properties could be explained only by Fe 3+ magnetic moments without a spin-state change of Co 3+ at x ≥ 0.15. [12][13][14] However, for M = Cr 3+ with an unfilled e g orbital, powder magnetization and neutron diffraction studies suggested that the Co 3+ LS state is maintained at x ≥ 0.1. 23 For M = Mn with an unfilled e g orbital, X-ray absorption spectroscopy studies revealed that Mn doping generates a set of Mn 4+ and Co 2+ pair for each Mn ion (electron doping), and powder magnetization studies suggested that magnetism arises from Mn 4+ and Co 2+ without magnetic Co 3+ .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 For M = Fe 3+ with filled e g orbitals, powder magnetization measurements, neutron diffraction, and Mössbauer spectroscopy all indicated that the magnetic properties could be explained only by Fe 3+ magnetic moments without a spin-state change of Co 3+ at x ≥ 0.15. [12][13][14] However, for M = Cr 3+ with an unfilled e g orbital, powder magnetization and neutron diffraction studies suggested that the Co 3+ LS state is maintained at x ≥ 0.1. 23 For M = Mn with an unfilled e g orbital, X-ray absorption spectroscopy studies revealed that Mn doping generates a set of Mn 4+ and Co 2+ pair for each Mn ion (electron doping), and powder magnetization studies suggested that magnetism arises from Mn 4+ and Co 2+ without magnetic Co 3+ .…”
Section: Introductionmentioning
confidence: 99%
“…11 Moreover, Co-site Fe doping induces weak ferromagnetism and a large magnetic anisotropy. [12][13][14] The Sr-doping phenomena were proposed [15][16][17] and established 18,19 to microscopically originate from ferromagnetic spin-state polarons, which refer to spin clusters consisting of a core radical Co 4+ ion and its surrounding magnetic-spin-state Co 3+ ions changing from the LS state. 20 The driving force is thought to be the double exchange interactions between Co 3+ and Co 4+ ; an electron is excited from the t 2g to e g orbital in Co 3+ (LS to IS) and then hops between the Co 3+ and Co 4+ e g orbitals.…”
Section: Introductionmentioning
confidence: 99%